CHINESE MIGRATION TO KAZAKHSTAN: CAUSES, KEY TRENDS, AND PROSPECTS - SADOVSKAYA, Elena (CENTRAL ASIA AND THE CAUCASUS, 2008)
The “Chinese miracle” phenomenon has many dimensions (dynamic economic growth, trade expansion, and huge demo-graphic potential) that have already attracted the attention of politicians and academics from many countries. Central Asia, and Kazakhstan as part of the region that borders on the People’s Republic of China in the east, has even more important reasons to scrutinize its trade and economic relations with China, related regional and national security issues, as well as the demographic pressure its neighbor is exerting on it. Today the Republic of Kazakhstan has been paying much more attention to its economic relations which China, which are being carefully studied and analyzed. Unfortunately, this cannot be said about the demographic and migration proc-esses underway between the two countries. How is Kazakhstan affected by the “demographic giant” it has for a neighbor? Is this intensifying migration to and from Kazakhstan? What are the prospects for Chinese migration to the republic? These questions should be carefully analyzed to create an information and analytical basis on which all sorts of policy, including migration policy, can stand. I have posed myself the task of analyzing the key causes of migration both in the country of origin and in the country of destination and looking at the main descriptions and specific features of various types of migration to outline the prospects for Chinese migration to Kazakhstan. The People’s Republic of China is one of the most dynamically developing countries. In recent years Beijing has been rapidly expanding its economic presence in Central Asia and Kazakhstan in particular, as well as building up its share in Kazakhstan’s international trade and economic relations.n the last seven years the trade turnover between them has been rapidly increasing with respect to both growth rate and absolute figures. Between 1999 and 2005, Kazakhstan increased its export to China over 5.2-fold, while China’s export to Kazakhstan grew 15.7-fold. The trade turnover between China and Kazakhstan grew 6.7-fold over the same period.1 In the last three years China moved to third place among Kazakhstan’s foreign trade partners in terms of percentage, however the structure of their trade can hardly be called balanced. Kazakhstan mainly sells China crude oil, ferrous metals, and copper, while China sends consumer goods (clothes, footwear, domestic electric appliances, and foodstuffs) to Kazakhstan. Much of what arrives in Kazakh-stan is brought by so-called shuttle traders.2